Developing frugal living character through the Piil Pesenggiri parenting model - Risma Margaretha Sinaga; Novia Fitri Istiawati; Tiara Oktavia; Ishbilya Safira (Indonesian Journal of Educational Development (IJED), 2026)
Global social and economic changes, intensified by digital access and consumer culture, encourage adolescents to adopt consumptive behaviors and weaken prudent personal financial management. Therefore, character education that promotes frugal living, self-control, and wise resource management needs to be strengthened through culturally grounded parenting practices. This study aimed to develop and examine a Piil Pesenggiri-based parenting module to foster students' frugal living character. The study employed a research and development (R&D) approach using the ADDIE model and was conducted at SMA YP Unila Bandar Lampung. A total of 72 students were selected through purposive sampling and divided into experimental and control groups. Data were collected through observation, questionnaires, and documentation, and analyzed using paired-sample t-tests and N-gain analysis. The results showed a significant improvement in the experimental group from pretest to posttest with a high N-gain score, while the control group showed only a slight increase. These findings indicate that the Piil Pesenggiri-based parenting module is effective in strengthening students' frugal living character and supporting sustainable lifestyles.